Interest in following swimming training for achievement at club tirta alvita Yogyakarta - Suharjana Suharjana; Sumarjo Sumarjo; Muhamad Ichsan Sabillah; Ardhika Falaahudin (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2023)
Swimming is an achievement sport and recreational activity that aims to relieve mental stress by balancing physical and psychological conditions. The purpose of this study was to determine interest in participating in swimming training at Club Tirta Alvita Yogyakarta. The type of research used in this research is descriptive quantitative research. The population in this study were children taking swimming lessons at the Tirta Alvita Yogyakarta Club with a total of 21 athletes. The sampling technique in this study used a total sampling technique. The sample in this study amounted to 21 athletes. Data analysis in this study uses a Likert scale. Data analysis used in this research is quantitative descriptive statistical analysis. From the results of the study showed that the results of interest in swimming training with a percentage of